Parents' nonstandard work and child wellbeing: a critical review of the existing literature - Li, Jianghong; Johnson, S.; Han, W.; Andrews, S.; Kendall, Garth; Strazdins, L.; Dockery, Alfred Michael (Curtin Business School, 2012)
The rising prevalence of nonstandard work among parents in the era of the 24-hour/7-day economy in developed countries has raised a concern about its possible impacts on children’s health and development. This paper provides a comprehensive and critical review of literature on this topic. To date researchers have examined (a) three developmental outcomes: mental health and behavioral problems, cognitive development, and childhood obesity; (b) family processes: parental time spent with children, parental monitoring, parent-child closeness, and the home environment and (c) other child outcomes: school engagement, extracurricular activities, and sleep patterns. Findings from research that used rigorous methodology show consistent associations between nonstandard work and poor child outcomes. This association is more pronounced in disadvantaged families and magnified when parents work nonstandard hours full-time. A similar association was found between nonstandard work and family processes. The paper discusses the strengths and limitations of existing research and directions for future research.